Drug-drug interactions as a result of co-administering Δ9-THC and CBD with other psychotropic agents. Issue 1 (2nd January 2018) - Rong, Carola; Carmona, Nicole E.; Lee, Yena L.; Ragguett, Renee-Marie; Pan, Zihang; Rosenblat, Joshua D.; Subramaniapillai, Mehala; Shekotikhina, Margarita; Almatham, Fahad; Alageel, Asem; Mansur, Rodrigo; Ho, Roger C.; et al.
ABSTRACT: Introduction : To determine, via narrative, non-systematic review of pre-clinical and clinical studies, whether the effect of cannabis on hepatic biotransformation pathways would be predicted to result in clinically significant drug-drug interactions (DDIs) with commonly prescribed psychotropic agents. Areas covered : A non-systematic literature search was conducted using the following databases: PubMed, PsycInfo, and Scopus from inception to January 2017. The search term cannabis was cross-referenced with the terms drug interactions, cytochrome, cannabinoids, cannabidiol, and medical marijuana . Pharmacological, molecular, and physiologic studies evaluating the pharmacokinetics of Δ 9 -tetrahydrocannabinol (Δ 9 -THC) and cannabidiol (CBD), both in vitro and in vivo, were included. Bibliographies were also manually searched for additional citations that were relevant to the overarching aim of this paper. Expert opinion : Δ 9 -Tetrahydrocannabinol and CBD are substrates and inhibitors of cytochrome P450 enzymatic pathways relevant to the biotransformation of commonly prescribed psychotropic agents. The high frequency and increasing use of cannabis invites the need for healthcare providers to familiarize themselves with potential DDIs in persons receiving select psychotropic agents, and additionally consuming medical marijuana and/or recreational marijuana.